Circulating adipokine levels and preeclampsia: A bidirectional Mendelian randomization study - Chen, Xiaoyan; Liu, Zhaoming; Cui, Jingen; Chen, Xiaolan; Xiong, Jing; Zhou, Wei (Frontiers in Genetics, 2022)
Background: Several observational studies have demonstrated that significantly rising circulating adipokine levels are pervasive in preeclampsia or eclampsia disorder (or preeclampsia toxemia (PET)). However, it remains unclear whether this relationship is causal. In this study, we sought to elucidate the causal effects of circulating adipokine levels on PET. Methods: Summary-level data and independent genetic variants strongly associated with common adipokine molecule (adiponectin, leptin, resistin, sOB-R, and PAI-1) levels were drawn from public genome-wide association study (GWASs). Additionally, the corresponding effects between instrumental variables and PET outcomes were acquired from the FinnGen consortium, including 4,743 cases and 136,325 controls of European ancestry. Subsequently, an inverse-variance weighted (IVW) approach was applied for the principal two-sample Mendelian randomization (MR) and multivariable MR (MVMR) analyses. Various complementary sensitivity analyses were then carried out to determine the robustness of our models. Results: The results of the IVW method did not reveal any causal relationship shared across genetically predisposed adipokine levels and PET risk (for adiponectin, OR = 0.86, 95% CI: 0.65–1.13, p = 0.274). Additionally, no significant associations were identified after taking into account five circulating adipokines in MVMR research. Complementary sensitivity analysis also supported no significant associations between them. In the reverse MR analysis, genetically predicted PET risk showed a suggestive association with elevating PAI-1 levels by the IVW method (Beta = 0.120, 95% CI: 0.014, 0.227, p = 0.026). Furthermore, there were no strong correlations between genetic liability to PET and other adipokine levels (p > 0.05). Conclusion: Our MR study did not provide robust evidence supporting the causal role of common circulating adipokine levels in PET, whereas genetically predicted PET may instrumentally affect PAI-1 levels. These findings suggest that PAI-1 may be a useful biomarker for monitoring the diagnosis or therapy of PET rather than a therapeutic target for PET.